KM3Net time calibration - Coniglione, R.; Creusot, A.; Di Palma, I.; Guderian, D.; Hofestädt, Jannik; Riccobene, G.; Sánchez Losa, A. (Proceedings of Science, 2019)
The KM3NeT Collaboration aims at the construction of a distributed research infrastructure under the Mediterranean Sea that will host two underwater neutrino detectors: ARCA and ORCA. They are optimised to detect neutrinos using the Cherenkov technique and will play an important role in the detection of high energy astrophysical neutrinos, ARCA, and in the study of the neutrino mass hierarchy exploiting the flux of atmospheric neutrinos, ORCA. Both detectors share the same technology: thousands digital optical modules, each hosting 31 3-inch photomultipliers, distributed along tall detection units. The main difference is the distance between the optical modules, optimised to meet the requirements of the different scientific objectives. The reconstruction of the neutrino direction exploits the Cherenkov photons emitted along the path of the charged particles produced in the neutrino interactions and requires a nanosecond synchronisation between the photomultipliers in order to get high angular resolution. This contribution describes the accurate time calibration procedures developed to synchronise the time references of the photomultipliers within an optical module and of each optical module within the detection unit and also between detection units.
CRIS-Team Scopus Importer:2024-12-16